Genetically-engineered pigs as sources for clinical red blood cell transfusion: What pathobiological barriers need to be overcome?. (May 2019) - Smood, Benjamin; Hara, Hidetaka; Schoel, Leah J.; Cooper, David K.C.
Abstract: An alternative to human red blood cells (RBCs) for clinical transfusion would be advantageous, particularly in situations of massive acute blood loss (where availability and compatibility are limited) or chronic hematologic diseases requiring frequent transfusions (resulting in alloimmunization). Ideally, any alternative must be neither immunogenic nor pathogenic, but readily available, inexpensive, and physiologically effective. Pig RBCs (pRBCs) provide a promising alternative due to their several similarities with human RBCs, and our increasing ability to genetically-modify pigs to reduce cellular immunogenicity. We briefly summarize the history of xenotransfusion, the progress that has been made in recent years, and the remaining barriers. These barriers include prevention of (i) human natural antibody binding to pRBCs, (ii) their phagocytosis by macrophages, and (iii) the T cell adaptive immune response (in the absence of exogenous immunosuppressive therapy). Although techniques of genetic engineering have advanced in recent years, novel methods to introduce human transgenes into pRBCs (which do not have nuclei) will need to be developed before clinical trials can be initiated.